Mal-operation analysis of LCC-HVDC protection schemes in simulation studies due to inaccurate transmission line modelling. Issue 4 (2nd October 2022) - Marvasti, Farzad Dehghan; Mirzaei, Ahmad
ABSTRACT: Protection in HVDC transmission lines, considering the significant amount of energy being transferred, has an undeniable importance on integrity of power systems. Due to unavailability of real HVDC transient data for protection studies, accurate modelling of HVDC systems through simulation software is the most practical alternative. One crucial part of a detailed transient simulation study is accurate line modelling, which, if not performed properly, can invalidate the results and conclusions. Therefore, in this study, three of the most accepted line models, namely the frequency-dependent, Bergeron and π -section line models, will be discussed, and their impact on the performance of some of the most accepted HVDC protection methods will be investigated. In comparison to the frequency-dependent line model, which produces the most accurate response, other line models are such inaccurate that their responses in simulation studies are not usable for designing a reliable protection scheme. The simulation study shows that some of the distance or boundary protection methods, designed based on integrating a Bergeron or π -section line model into their studies, can be completely unreliable. The validity of these claims is assessed based on the modified bipolar version of the CIGRE HVDC test system, simulated in the PSCAD/EMTDC software.